The effect on stock price inclusion or exclusion from the FTSE4good Bursa Malaysia - Mohd Sabri, Heidi Maryssa; Mohd Nasarudin, Ahmad Fawwaz; Azrai Azaimi Ambrose, Azniza Hartini (Universiti Teknologi Mara (UiTM), 2022)
The fight for sustainability in finance is a conundrum that divides opinions among market participants. Given its potential hefty increase in the cost of operation, there is a perception that a sustainable investment could slow down financial returns. This leads one to wonder how market participants will respond to sustainable-related announcements. To address the issue, this study investigated the sensitivity of investors towards the Environmental, Social, and Governance (ESG) movement in Malaysia by examining the announcement effect of inclusion or exclusion of a firm from the FTSE4Good Bursa Malaysia Index by employing an event study analysis. Our findings indicated that investors are sensitive to both announcements, but stock price adjusts faster towards deletion announcements compared to inclusion announcements from the index. This study enriches the literature on semi-strong market efficiency although slight evidence suggests possible overreaction and momentum trading. The study also showed that Malaysian investors are sensitive to ESG announcements, as the inclusion (exclusion) of stock is met with positive (negative) effects on returns.